2019
DOI: 10.1111/bjdp.12305
|View full text |Cite
|
Sign up to set email alerts
|

Aware and tuned to care: Children with better distress recognition and higher sympathy anticipate more guilt after harming others

Abstract: Helping children recognize the distress of their victims and feel sympathy may facilitate the optimal socialization of ethical guilt. With a sample of 150 eight-year-olds, we tested the main and interactive relations of distress recognition and sympathy to ethical guilt after hypothetically stealing and pushing. Better fear recognition and higher sympathy were uniquely associated with higher ethical guilt. The link between fear recognition and ethical guilt was stronger in children with higher sympathy. Beyond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Children's reasoning for each emotion was coded based on previous research (Colasante et al., 2019; Malti, Gummerum et al., 2009). Each reason was coded into one of four categories: ethical reasons outlining principles of fairness, justice, or references to the welfare of others (e.g., “It's not fair to steal”; “He'll be sad”), sanction‐oriented/conventional reasons reflecting censure from authority figures or peers, concerns over anticipated rule violations, or disruptions to group functioning (e.g., “I'll get in trouble by the teacher”; “It's against the rules”), self‐focused responses reflecting self‐centered benefits or excuses for the behavior (e.g., “I love chocolate”; “He didn't want it anyway”), or uncodable / other responses (e.g., “Because”; “It's bad”; “It's not nice”).…”
Section: Methodsmentioning
confidence: 99%
“…Children's reasoning for each emotion was coded based on previous research (Colasante et al., 2019; Malti, Gummerum et al., 2009). Each reason was coded into one of four categories: ethical reasons outlining principles of fairness, justice, or references to the welfare of others (e.g., “It's not fair to steal”; “He'll be sad”), sanction‐oriented/conventional reasons reflecting censure from authority figures or peers, concerns over anticipated rule violations, or disruptions to group functioning (e.g., “I'll get in trouble by the teacher”; “It's against the rules”), self‐focused responses reflecting self‐centered benefits or excuses for the behavior (e.g., “I love chocolate”; “He didn't want it anyway”), or uncodable / other responses (e.g., “Because”; “It's bad”; “It's not nice”).…”
Section: Methodsmentioning
confidence: 99%
“…Children’s reasoning for each emotion was initially coded into one of four categories using a coding scheme adapted from prior research (Colasante et al, 2019; Malti, Gummerum, et al, 2009). Ethical reasons reflected principles of fairness, justice, or references to the welfare of others (e.g., “It’s not fair to steal”; “He’ll be sad”).…”
Section: Methodsmentioning
confidence: 99%
“…If this "care" hypothesis is correct, we would expect happy victimizer responses to be associated with a reduced capacity for sympathy, a complex social emotion entailing feelings of sorrow and concern for others' wellbeing (Eisenberg et al, 2014). In support of this view, research during middle childhood and adolescence has shown that, compared with less sympathetic youth, those higher in sympathy expect to feel more intense negative emotions (e.g., guilt) after hypothetically harming others (Colasante et al, 2019;Daniel et al, 2014). Longitudinal research by Krettenauer et al, (2014) further found that self-and caregiverreported sympathy at age 15 were negatively associated with happy victimizing responses concurrently and in early adulthood.…”
Section: Psychological Accounts Of Happy Victimizationmentioning
confidence: 99%